ANALISIS PENGARUH GAME ONLINE TERADAP PRILAKU SOSIAL ANAK SEKOLAH DASAR - Nadiya, Anggun; Ummul Izzah, Fatiyah; Prezilia Bahri, Fiolga; Mayang Sari, Tri; Tasya Jadidah, Ines (JIMR : Journal Of International Multidisciplinary Research, 2024)
The research conducted has the aim of (1) understanding the consequences and also the impact of online games (2) describing how to overcome students who are addicted to online games (3) investigating why children are mostly interested in online games rather than learning.  The method used in this research is qualitative method. The qualitative method is a descriptive observation that combines as much information as possible about a topic that has not supported the quality of teaching. Qualitative research is characterized by direct research from direct data. Research is shown in the form of pictures, words, and numbers. This research method is not made up by researchers, and data analysis is taken in accordance with real events in the field. The population and sample of this study included all students of class IV A, as many as 20 people with details of 9 boys and 11 girls. The research was conducted at SDN 39 Palembang. The results of the study stated that the impact of playing games can hinder the development of children's personality, for example including rebellious behavior, arguing, fighting, individualism, and lack of care for others.